Penguatan Ketahanan Keluarga melalui Edukasi Bahaya Judi Online di Desa Kopen, Wonogiri - Hidayah, Safina Octavia; Fayola, Tabina Triadinda; Riyani, Adelweiss Putri; Rustandi, Agniyya Muhshi; Nursofyani, Aziizah; Samara, Farhan Habibie; Maulana, Muhammad Firlan; Qodari, Sahrul; Arif, Ridi (Jurnal Pusat Inovasi Masyarakat, 2025)
The community of Kopen Village faces challenges to family resilience, particularly in family resource management, communication, and digital risk control such as online gambling. This community service program aimed to enhance participants' understanding of family resilience and mitigate the dangers of online gambling that threaten family harmony. The activity was conducted in collaboration with the TP-PKK of Kopen Village and involved 16 participants representing all hamlets.  The methods used were interactive socialization, discussions supported by a pop-up family resilience house visual media, and quantitative measurement through pre-tests and post-tests. A guide materials booklet was also developed for the sustainability program. The results demonstrated a significant increase in understanding, with all participants scoring in the high category after the activity compared to the pre-test scores. The interactive approach, coupled with real-life examples, successfully strengthened participants’ awareness of the strategic role of the family in managing digital risks. The guide material produced ensures the program has a sustainable impact on literacy and strengthen family resilience in Kopen Village.